Assessment of the contribution of the IHC4+C score to decision making in clinical practice in early breast cancer - Barton, S (Nature Publishing Group, 2012)
BACKGROUND: The immunohistochemical (IHC) 4+C score is a cost-effective prognostic tool that uses clinicopathologic factors and four standard IHC assays: oestrogen receptor (ER), PR, HER2 and Ki67. We assessed its utility in personalising breast cancer treatment in a clinical practice setting, through comparison with Adjuvant! Online (AoL) and the Nottingham Prognostic Index (NPI). METHODS: We prospectively gathered clinicopathologic data for postmenopausal patients with hormone receptor-positive, HER2-negative, N0-3 resected early breast cancer treated consecutively at our institution. We retrospectively calculated and compared prognostic scores. The primary endpoint was the proportion of patients reclassified from AoL-defined intermediate-risk by application of the IHC4+C score. RESULTS: The median age of the 101 patients included in the analysis was 63. In all, 15 of the 26 patients classified as intermediate-risk by AoL were reallocated to a low-risk group by application of the IHC4+C score and no patient was reclassified as high-risk group. Of the 59 patients classified as intermediate-risk group by the NPI, 24 were reallocated to a low-risk group and 13 to a high-risk group. CONCLUSION: IHC4+C reclassifies more than half of the patients stratified as being in intermediate-risk group by the AoL and NPI. The use of IHC4+C may substantially improve decision-making on adjuvant chemotherapy.